Revision of the species of Hydraena Kugelann (Coleoptera: Hydraenidae) from Palawan and Busuanga, with descriptions of eleven new species, and redescription of Hydraena (Hydraenopsis) scabra d’Orchymont, 1925 - Freitag, Hendrik; Jäch, Manfred A. (Zootaxa, 2007)
The species of Hydraena Kugelann from the Philippine Islands of Palawan and Busuanga are revised. Eleven new species are described: Hydraena (Hydraenopsis) busuanga Freitag & Jäch, sp. n., H. (Hydraenopsis) castanescens Freitag & Jäch, sp. n., H. (Hydraenopsis) claudia Freitag & Jäch, sp. n., H. (Hydraenopsis) hosiwergi Freitag & Jäch, sp. n., H. (Hydraenopsis) jojoorculloi Freitag & Jäch, sp. n., H. (Hydraenopsis) kodadai Freitag & Jäch, sp. n., H. (Hydraenopsis) manguao Freitag & Jäch, sp. n., H. (Hydraenopsis) nielshaggei Freitag & Jäch, sp. n., H. (Hydraenopsis) palawanensis Freitag & Jäch, sp. n., H. (Hydraenopsis) pseudopalawanensis Freitag & Jäch, sp. n., and H. (Hydraenopsis) zetteli Freitag & Jäch, sp. n. Hydraena (Hydraenopsis) scabra d’Orchymont, 1925 is redescribed and its distribution in the Philippines documented. A key to the Hydraena species of Palawan and Busuanga is provided.